2004
DOI: 10.1164/rccm.200307-964oc
|View full text |Cite
|
Sign up to set email alerts
|

Human Bronchial Smooth Muscle Cell Lines Show a Hypertrophic Phenotype Typical of Severe Asthma

Abstract: We developed clonal cell lines of human bronchial smooth muscle origin by retroviral transduction of temperature-sensitive simian virus 40 large tumor (T) antigen. These cells show increased growth potential at 33 degrees C, but on shift to the nonpermissive temperature (39 degrees C), they show diminished or arrested growth. In addition to the expected reduction in the level of large T antigen, cells shifted to 39 degrees C show increased expression of the cyclin-dependent kinase inhibitor p21(Waf1/Cip1), cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…We speculate that the preferential inhibitory effect of eIF2⑀ siRNA on ␣-actin and SM22 translation relates to the relatively high levels of contractile apparatus mRNA in the cell, compared with ␤-actin, ERK, or GAPDH. We have previously found that steady-state ␣-actin and SM22 mRNA levels are high in unstimulated airway smooth muscle cells (35,36). This level would be further increased following GSK-3␤ inhibition, which, as noted above, stimulates ␣-actin transcription.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We speculate that the preferential inhibitory effect of eIF2⑀ siRNA on ␣-actin and SM22 translation relates to the relatively high levels of contractile apparatus mRNA in the cell, compared with ␤-actin, ERK, or GAPDH. We have previously found that steady-state ␣-actin and SM22 mRNA levels are high in unstimulated airway smooth muscle cells (35,36). This level would be further increased following GSK-3␤ inhibition, which, as noted above, stimulates ␣-actin transcription.…”
Section: Discussionmentioning
confidence: 66%
“…Two models employing cell cycle arrest (long term serum deprivation and withdrawal of SV40 large T antigen) demonstrate increases in cell size and contractile protein accumulation without a corresponding increase in mRNA (35,36), again suggestive of posttranscriptional control. In the latter model, as with TGF-␤-treated cells, hypertrophy did not occur in cells infected with a retrovirus encoding a phosphorylation site mutant of 4E-BP1 that dominantly inhibits eIF4E, suggesting that phosphorylation of 4E-BP, eIF4E release, and cap-dependent protein syn-FIGURE 7.…”
Section: Discussionmentioning
confidence: 98%
“…An increase in the volume of smooth muscle does not necessarily mean increased force development, since proliferating or secretory smooth muscle may have reduced contractility [38,39]. A hypercontractile phenotype is observed in vitro after serum deprivation or other manipulations of cultured smooth muscle cells [39].…”
Section: Smooth Musclementioning
confidence: 99%
“…A hypercontractile phenotype is observed in vitro after serum deprivation or other manipulations of cultured smooth muscle cells [39]. It is not clear whether the ''normal'' state of smooth muscle in situ is secretory, contractile or hypercontractile.…”
Section: Smooth Musclementioning
confidence: 99%
“…In the first model, canine tracheal myocytes demonstrated high levels of SM22 and smooth muscle myosin heavy chain (smMHC) mRNA expression during rapid cell proliferation but only accumulated contractile protein during long-term serum deprivation (81). In the second model, airway smooth muscle cells conditionally immortalized with a thermolabile simian virus 40 (SV40) large tumor (T) antigen demonstrated increased a-smooth muscle actin and MLCK protein abundance but not mRNA expression upon shift to the nonpermissive temperature, which inactivates large T antigen and induces expression of p57 and p21 Waf1/Cip1 (82). More recent studies have used physiologic stimuli, such as cardiotrophin (34) and TGF-b (40).…”
Section: Biochemical Mechanisms Regulating Airway Smooth Muscle Hypermentioning
confidence: 99%